...como se fosse um deles. Almirante Aragão:memórias, silêncios e ressentimentos - Almeida, Anderson da Silva (2014)
The thesis is a biographical approach about one of the most polemical militaries of recent history of the Brazil. Member of the military summit of the Goulart’s government, Candido da Costa Aragão , militar from Paraíba who joined Armed Forces as a soldier in the 1920s, was the "eye of the hurricane" during the civil - military coup from 1964 and remains in the memories of many characters politicians of period just like "the man who didn’t react" or admiral who was involved with subordinates, "as if he was one of them”. Appositive to the newspapers showed in period before the coup, when his support was considered essential to strengthen called the military device of the president João Goulart, the same forces that supported Jango also contributed to the ostracism that marks the trajectory of the character investigated here. Called "Red Admiral" by his opponents and "Admiral of the people" by his supporters, Aragão who we present goes far beyond the moment of the coup, when he was challenged by Carlos Lacerda Governor and called assassin, incestuous ... Here we dive in his path along the exile and his passage by many countries, not just as a spectator but also as agent and privileged character in each context. The disputes in the Uruguayan exile with Leonel Brizola supported by Cuba, his cordial relationship with Carlos Marighella; their passage by China of Mao Zedong, Algeria, the war in Vietnam, Chile during government and the fall of Allende; Péron Argentina, Portugal of April 25, 1974, and Venezuela of Carlos Andrés Pérez, always in moments of strong social struggles in these countries, it also makes us privileged observers of events and ideological battles that marked the twentieth century. Memories, silences and resentments are presented not only as analytical categories, but as key concepts that help us to understand the character and the disputes of his time.